VD_FINDINFO HC / 2011 / 350 vom 17. Mai 2011 - VD Tribunal cantonal (2011)
CONTRAT DE TRAVAIL, TRANSACTIONACCORD, HARCÈLEMENT PSYCHOLOGIQUE | 321c al. 2 CO, 321c al. 3 CO, 328 CO, 329 al. 3 CO, 336c CO, 341 al. 1 CO, 361 CO, 49 al. 1 CO, 236 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH), 405 al. 1 CPC (CH)